The use of technology to enhance the supply chain process within operations departments - Amine, Hicham; Ayouche, Najwa; Mesnaoui, Abdelouahab (IJRDO - Journal of Business Management, 2017)
The purpose of this study is to provide a basis for upgrading and strengthening EDI capabilities by meeting specific and phased goals. Its primary objective is to replace the traditional SeeBeyond translation tool used for MaSys EDI processing. This aim needs to be successfully achieved before W&F starts the SeeBeyond contract extension process after the latter’s expiry, which puts a hard deadline for our study. The replacement of SeeBeyond needs to be done as simply and cleanly as possible so as to minimize potential disruptions and changes to the MaSys application. Another objective of our BRDis to retrofit QUE to potentially use the new translation tool (project scope and timing to be approved). This is intended to reduce the programming effort to configure and maintain EDI processing in QUE, and also to standardize Integra’s EDI translation processing to a single platform. We also envision, through our project, to upgrade QUE’s business process and technology capabilities such that providers can submit claims via EDI to Integra (project scope and timing to be approved). This will significantly improve the service to providers by removing both duplicate keying and process friction. Since the primary focus of this project is the replacement of SeeBeyond for MaSys EDI, we have undertaken a thorough process of evaluating alternative products during February and March 2016. After extensive research, we have decided to select Edifecs which is also used by Tufts Health Plan (THP)